1995
DOI: 10.1016/0735-1097(95)00297-9
|View full text |Cite
|
Sign up to set email alerts
|

Stress testing with closed-loop arbutamine as an alternative to exercise

Abstract: In detecting documented coronary artery disease, the sensitivity of arbutamine testing was equal to that of exercise for the electrocardiographic end point of ST segment change alone. Arbutamine testing was significantly superior to exercise testing for either ST change or angina or for angina alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
2

Year Published

1995
1995
2002
2002

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(8 citation statements)
references
References 22 publications
1
5
0
2
Order By: Relevance
“…The safety profile for arbutamine as described in these studies (9,10,18) is similar to that reported for dobutamine (28,34,36) and is consistent with the use of a catecholamine as a pharmacological stress agent. The most frequent adverse events reported with arbutamine were tremor (8-23%), flushing (1O-15%), headache (8-12%), arrhythmias ( 6 7 % ) , dizziness (1-8%) and hypotension (47%).…”
Section: Clinical Experiencesupporting
confidence: 80%
See 1 more Smart Citation
“…The safety profile for arbutamine as described in these studies (9,10,18) is similar to that reported for dobutamine (28,34,36) and is consistent with the use of a catecholamine as a pharmacological stress agent. The most frequent adverse events reported with arbutamine were tremor (8-23%), flushing (1O-15%), headache (8-12%), arrhythmias ( 6 7 % ) , dizziness (1-8%) and hypotension (47%).…”
Section: Clinical Experiencesupporting
confidence: 80%
“…The most frequent arrhythmias reported were premature ventricular complexes (3%) and potentially significant arrhythmias, such as non-sustained ventricular tachycardia, supraventricular tachycardia, and atrial fibrillation, were rare (<2.0%). Two patients in the ECG study experienced ventricular fibrillation (10). In one case, the arrhythmia occurred after the investigator restarted the arbutamine infusion following its termination by the GenESA Device because of a decrease in heart rate (the heart rate saturation phenomenon described earlier).…”
Section: Clinical Experiencementioning
confidence: 97%
“…Arbutamine is a recently developed sympathomimetic which has been shown to be a safe and effective method of detecting coronary artery disease [7][8][9][10][11]. The present study compared the physiological responses occurring during arbutamine and conventional exercise stress testing.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, arbutamine produces important physiological and metabolic effects which have been proven to be of value in the diagnosis of coronary artery disease [10,11], especially when there are contra-indications to conventional treadmill or bicycle exercise protocols. Arbutamine infusion is associated with an increase in the following parameters : heart rate, systolic blood pressure,…”
Section: Discussionmentioning
confidence: 99%
“…It has both inotropic and chronotropic effects, simulating some of the effects of exercise, including increases in cardiac contractility, systolic blood pressure and heart rate [8]. A computercontrolled ' closed-loop ' system is used to deliver the arbutamine, based upon the heart rate responses [9][10][11].…”
Section: Introductionmentioning
confidence: 99%